Mitochondrial Genomes of Hemiarma marina and Leucocryptos marina Revised the Evolution of Cytochrome c Maturation in Cryptista - Nishimura, Yuki; Kume, Keitaro; Sonehara, Keito; Tanifuji, Goro; Shiratori, Takashi; Ishida, Ken-ichiro; Hashimoto, Tetsuo; Inagaki, Yuji; Ohkuma, Moriya (Frontiers in Ecology and Evolution, 2020)
Two evolutionarily distinct systems for cytochrome c maturation in mitochondria—Systems I and III—have been found among diverse aerobic eukaryotes. System I requires a set of proteins including mitochondrion-encoded CcmA, CcmB, CcmC and CcmF (or a subset of the four proteins). On the other hand, System III is operated exclusively by nucleus-encoded proteins. The two systems are mutually exclusive among eukaryotes except a single organism possessing both. Recent advances in understanding both diversity and phylogeny of eukaryotes united cryptophytes, goniomonads, Hemiarma marina, kathablepharids and Palpitomonas bilix into one of the major taxonomic assemblages in eukaryotes (Cryptista). Among the lineages/species in Cryptista, the mitochondrial genomes (mtDNAs) have been completed for multiple cryptophytes, a goniomonad and P. bilix, and ccm genes were found solely in the P. bilix mtDNA. Nevertheless, we have been unsure whether H. marina and/or kathablepharids use System I for cytochrome c maturation, as no mtDNA was available for either of the two cryptist members. In this study, we determined the complete sequences of the mtDNAs of H. marina and a kathablepharid Leucocryptos marina, and found ccmA, ccmC and ccmF in the former genome. Curiously, the ccm genes found in the H. marina mtDNA showed no phylogenetic affinity to the P. bilix homologs, unfavoring vertical inheritance of the ccm genes in the mtDNA evolution in Cryptista. Finally, we propose a revised version for the evolution of cytochrome c maturation systems in Cryptista by incorporating the mtDNA data obtained in this study.